Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/rb/rbx009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mechanical loads on the degradation of aliphatic biodegradable polyesters

Abstract: Aliphatic biodegradable polyesters have been the most widely used synthetic polymers for developing biodegradable devices as alternatives for the currently used permanent medical devices. The performances during biodegradation process play crucial roles for final realization of their functions. Because physiological and biochemical environment in vivo significantly affects biodegradation process, large numbers of studies on effects of mechanical loads on the degradation of aliphatic biodegradable polyesters ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 135 publications
0
28
0
Order By: Relevance
“…These environmentally friendly polymers could be classified into three different groups with different environmental connotations [8]. One group is composed of biodegradable petroleum-derived polymers such as most aliphatic polyesters, i.e., poly(ε-caprolactone)—PCL, poly(butylene succinate)—PBS, poly(glycolic acid)—PGA and so on [9,10,11]. Although they are petroleum-derived polymers, they show interest from an environmental standpoint as they can be disintegrated in controlled compost soil conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These environmentally friendly polymers could be classified into three different groups with different environmental connotations [8]. One group is composed of biodegradable petroleum-derived polymers such as most aliphatic polyesters, i.e., poly(ε-caprolactone)—PCL, poly(butylene succinate)—PBS, poly(glycolic acid)—PGA and so on [9,10,11]. Although they are petroleum-derived polymers, they show interest from an environmental standpoint as they can be disintegrated in controlled compost soil conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1 , the control non-irradiated PLGA presented higher molecular weights ( M n = 253,900 and M w = 460,400) while the irradiated membranes ( Table 2 ) showed a significant decrease in the molecular weights ( M n = 75,000 and M w =156,300), revealing that sterilization by gamma irradiation caused a strong PLGA degradation (66% of M w lost). High molecular weight polymers, as the non-irradiated PLGA used in the present study, have long chains, being more susceptible to the drastic decrease of average molecular weight when exposed to hydrolytic fluids [ 28 ]. In this regard, a drastic decrease in the molecular weight of the non-irradiated nonwoven immersed in saliva at 30 days was observed ( Table 1 ) when compared to the irradiated nonwoven immersed in saliva at the same time point, both relative to each control (first lines Table 1 and Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The slight increase in M n and M w observed for two samples after immersion at 15 days in SBS and DMEM is under the expected uncertainty for the GPC technique and, since there is no reason for such an increase, it was considered an experimental error. Considering mass loss during degradation in solutions, Perron et al showed that the percentage of water absorption after immersion of PLGA (85:15) in phosphate buffer saline (PBS) and distilled water (dH 2 O) after 84 day, were solution dependent: (i) after immersion in PBS solution, scaffolds water absorption increased from 0 to 100% after 7 days and remained constant for the other periods of degradation and (ii) the water uptake of the scaffold exposed to dH 2 O varied from 0 to 150% after 7 days of degradation and increased up to 200% towards the end of the degradation study [ 28 ]. Authors observed that mass loss was within 4% throughout the full degradation period, and as mass loss water uptake decreases [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Degradation of the implants was faster in gap-bridged defects than in reinforced areas. A higher load may have changed the conformational strain energy and morphology of the implant, affecting the stability of the polymer [34]. In addition, it may lead to cracking of the microfibres, hence an increase in the surface area for the oxidative degradation induced by the host inflammatory response.…”
Section: Discussionmentioning
confidence: 99%